Translucent Solid Soap Preparation from Turmeric Rhizome Juice (Curcuma domestica Val.): Formulation and Physical Characterization - Aulia, Meisyah; Lubis, Minda Sari; Dalimunthe, Gabena Indrayani; Yuniarti, Rafita (Indonesian Journal of Science and Pharmacy, 2024)
The formulation and physical characterization of translucent solid soap preparations from turmeric rhizome juice (Curcuma domestica Val.) have been carried out. The manufacture of translucent soap was carried out by varying the concentration of turmeric rhizome juice from 0%, 2%, 4%, and 6% into the soap formula. The multi-physical tests of translucent soap preparations included organoleptic tests, pH tests, water content tests, foam stability height tests, irritation tests and preference tests. The obtained turmeric rhizome squeezed translucent soap had good characteristics and met the requirements as translucent soap because it had good hardness, appropriate water content, pH between 9-11, and good foam stability. The results of the skin irritation test of soap preparations of all concentration variations did not find any side effects in the form of redness, itching and roughness on the volunteer's skin so that all soap preparations with various comparisons were safe to use. The results of the preference test which included color, translucency, texture and aroma showed that on average the panelists liked the soap preparation with a turmeric rhizome juice concentration of 2%.